2019
DOI: 10.3390/polym11121997
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soybean Soluble Polysaccharide on the Formation of Glucono-δ-Lactone-Induced Soybean Protein Isolate Gel

Abstract: The effect of soybean soluble polysaccharide (SSPS) on the formation of glucono-δ-lactone (GDL)-induced soybean protein isolate (SPI) gel was investigated. Electrophoretic analysis showed the SSPS did not change the electrophoretic behavior of SPI during the formation of SPI gel. However, infrared analysis indicated the β-sheet content increased, and the contents of random coil and α-helix decreased in both cooked SPI and SPI gel. The SSPS and SPI might conjugate via the Maillard reaction according to the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 45 publications
2
4
0
Order By: Relevance
“…This might explain the softer texture of WPEG produced by TFU pretreatment as shown by hardness analysis. The effect of gel microstructure on gel properties has been reported by other researchers [ 42 , 43 , 44 ], and our previous results [ 4 , 8 , 15 ] also confirmed that the homogenous and compact gel network was associated with better gel properties and storage modulus.…”
Section: Resultssupporting
confidence: 88%
“…This might explain the softer texture of WPEG produced by TFU pretreatment as shown by hardness analysis. The effect of gel microstructure on gel properties has been reported by other researchers [ 42 , 43 , 44 ], and our previous results [ 4 , 8 , 15 ] also confirmed that the homogenous and compact gel network was associated with better gel properties and storage modulus.…”
Section: Resultssupporting
confidence: 88%
“…Similar results were observed in studies where polysaccharides were added to soybean protein isolate and whey protein to form complex gels. 62,63 They attributed this phenomenon to the tight binding of protein and polysaccharide molecules through electrostatic attraction and hydrogen bonding and hydrophobic interaction. This result corroborates our judgment that TPS can be filled into the pores of the gelatin network through non-covalent interactions, making the originally porous and unevenly distributed gelatin network dense and uniform, thereby improving the gel properties.…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
“…The observed differences in the protein composition and disulfide bond formation in the konjac starch and SPI mixture may be due to the creation of new hydrogen bonds, which could cause protein dissociation or refolding. This may lead to the transformation of intramolecular disulfide bonds into intermolecular disulfide bonds [48]. Additionally, the growth in the relative quantity of the g-g-g form of G-SPI could result from covalent binding between some of the SPI and polysaccharide molecules, forming intramolecular disulfide bonds [49].…”
Section: Disulfide Bond Conformational Analysismentioning
confidence: 99%